Efektivitas Alat Peraga Edukatif (APE) Balok Dalam Mengembangkan Kognitif Anak Usia Dini - Akhmad Shunhaji; Nur Fadiyah (Kopertais Wilayah I DKI Jakarta dan Banten, 2020)
The effectiveness of the use of teaching aids that are associated with cognitive development of early childhood, with the strategy of applying the method of playing blocks in the Kindergarten Plus Cinangka Sawangan Depok conducted by the teachers will determine the success of the effectiveness of the cognitive development of students, which are then developed routinely in accordance with the learning objectives It has been planned to be associated with the strategy of applying the method of playing blocks in accordance with basic competencies and learning indicators. Learning practices that use block media at TK Permata Plus are less than optimal due to the ratio of learners whose number exceeds the number of available beam props, so learning cannot be maximized. The active involvement of children is needed to improve their abilities and further research is needed from various variations to contribute to the learning problem. Playing with blocks can improve cognitive abilities of early childhood including: recognizing geometric shapes, recognizing colors. Make a Beam shape creation, sort objects based on five size or color seriations and classify objects into the same or similar group or in pairs with two variations.